Multiple-scattering calculations for layered phononic structures of nonspherical particles - G. Gantzounis; N. Papanikolaou; N. Stefanou (Physical Review B, 2011)
We present an extension of the layer-multiple-scattering method to phononic crystals of nonspherical particles in a homogeneous host medium by employing the extended-boundary-condition technique for the description of the individual scatterers. The efficiency of the method is demonstrated on specific examples of two- and three-dimensional periodic assemblies of spheroidal polymer particles in water and in silicon. We report a thorough analysis of the acoustic properties of these composites and emphasize aspects of the underlying physics that relate to the nonspherical shape of the particles.